2019
DOI: 10.1111/jcpe.13226
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported halitosis in a sample of Brazilians: Prevalence, associated risk predictors and accuracy estimates with clinical diagnosis

Abstract: Aims:To evaluate the prevalence of self-reported halitosis and its predictors, and to determine the accuracy estimates of self-reported measures with clinical evaluation of halitosis. Materials and Methods:This cross-sectional study comprised 5,420 individuals (teaching staff, administrative personnel and ongoing students from Federal University of Minas Gerais), who answered a structured questionnaire containing sociodemographic, medical and dental data, and self-reported halitosis measures.A subsample (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…This observation is in accordance with other studies reporting anamnesis as the main diagnostic tool used by dentists or hygienists [8]. The organoleptic method is considered the gold standard; however, it should be performed by a trained professional in order to be effective [23]. As self-reported halitosis measures can improve screening strategies, the systematic use of self-administered questionnaires may be helpful, even for untrained dentists [23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This observation is in accordance with other studies reporting anamnesis as the main diagnostic tool used by dentists or hygienists [8]. The organoleptic method is considered the gold standard; however, it should be performed by a trained professional in order to be effective [23]. As self-reported halitosis measures can improve screening strategies, the systematic use of self-administered questionnaires may be helpful, even for untrained dentists [23].…”
Section: Discussionsupporting
confidence: 85%
“…The organoleptic method is considered the gold standard; however, it should be performed by a trained professional in order to be effective [23]. As self-reported halitosis measures can improve screening strategies, the systematic use of self-administered questionnaires may be helpful, even for untrained dentists [23]. The use of such tools may be restricted due to lack of training and also because VSC measurement instruments are not available in most private practice offices.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as halitosis has always been associated with gingival bleeding in many studies. [46][47][48][49][50] Usually, untreated gingival inflammation will progress to periodontitis with the characteristic pocket formation with or without gingival recession. [2][3][4][5][6][7][8][9] A few (2.6%) of our participants had chronic periodontitis expressed as gingival recession measuring between 3-and 4-mm.…”
Section: Resultsmentioning
confidence: 99%
“…In a large-scale study conducted in Brazil, the specificity for self-reported halitosis was high for clinical and strong halitosis. 42 Another study by Pham concluded that self-estimation of halitosis corresponds well with the organoleptic scores, with almost half of the participants correctly scored their mouth odour with the examiners. 43 In the oral health field, self-reported questionnaires are a frequently used tool in epidemiological studies.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, other studies found that both the organoleptic scores and the self‐perceived halitosis are well correlated. In a large‐scale study conducted in Brazil, the specificity for self‐reported halitosis was high for clinical and strong halitosis 42 . Another study by Pham concluded that self‐estimation of halitosis corresponds well with the organoleptic scores, with almost half of the participants correctly scored their mouth odour with the examiners 43 .…”
Section: Discussionmentioning
confidence: 97%